ANALISIS KEPUASAN KONSUMEN TERHADAP PELAYANAN MINI MARKET INDOMARET CIPINANG ASEM DI KELURAHAN KEBON PALA KECAMATAN MAKASAR JAKARTA TIMUR - Sitanggang, Herpina Roulina; Sembiring, Carolina F.; Rajagukguk, Wilson (Fundamental Management Journal, 2016)
This study aims to determine how the level of customer satisfaction on service performance Indomaret Cipinang Asem. The data used in this study derived from primary data, ie data obtained by distributing questionnaires to 100 respondents. As for the secondary data obtained from the study of literature and other sources that is certainly related to this research. The method used in this study is the importance of performance analysisdengan using ANOVA tables for processing the data, while the data collection techniques using Likert scale questionnaire contained therein Cartesian diagram. Conclusions can be drawn based on the diagram Cartesian are attributes that are in quadrant A, the employees handling customer complaints properly, employees serve customers quickly, employees are scrupulous in airport shopping deals, priced accordingly between listed with the data in the computer, the availability of products in Indomaret Asem Cipinang complete, the product availability in Cipinang Indomaret Asem, the availability of adequate parking places. The attributes of the attribute that most influences customer dissatisfaction Indomaret Cipinang Asem is atibut 10 is a discrepancy between the price specified by the data on the computer. Advice can be given to Indomaret Cipinang Asem Kebon Pala is Better Indomaret Cipinang Asem Kebon Pala more attention and improve pelayananannya contained in the attributes in quadrant A, which mainly attributes 10 that is a discrepancy between listed with the data in the computer because these attributes important for customers but implementation in Cipinang Indomaret Asem not meet the interests of customers.